The Domestic Cat as a Large Animal Model for Characterization of Disease and Therapeutic Intervention in Hereditary Retinal Blindness - Kristina Narfström; Koren Holland Deckman; Marilyn Menotti-Raymond (Journal of Ophthalmology)
Large mammals, including canids and felids, are affected by spontaneously occurring hereditary retinal diseases with similarities to those of humans. The large mammal models may be used for thorough clinical characterization of disease processes, understanding the effects of specific mutations, elucidation of disease mechanisms, and for development of therapeutic intervention. Two well-characterized feline models are addressed in this paper. The first model is the autosomal recessive, slowly progressive, late-onset, rod-cone degenerative disease caused by a mutation in the CEP290 gene. The second model addressed in this paper is the autosomal dominant early onset rod cone dysplasia, putatively caused by the mutation found in the CRX gene. Therapeutic trials have been performed mainly in the former type including stem cell therapy, retinal transplantation, and development of ocular prosthetics. Domestic cats, having large human-like eyes with comparable spontaneous retinal diseases, are also considered useful for gene replacement therapy, thus functioning as effective model systems for further research.